2013
DOI: 10.1101/gr.156075.113
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of recessive disease genes: CNV contribution to carrier states and disease-causing alleles

Abstract: Over 1200 recessive disease genes have been described in humans. The prevalence, allelic architecture, and per-genome load of pathogenic alleles in these genes remain to be fully elucidated, as does the contribution of DNA copy-number variants (CNVs) to carrier status and recessive disease. We mined CNV data from 21,470 individuals obtained by array-comparative genomic hybridization in a clinical diagnostic setting to identify deletions encompassing or disrupting recessive disease genes. We identified 3212 het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 46 publications
1
57
0
Order By: Relevance
“…Genome-wide approaches have shown that rare variants are more common than previously thought [Coventry et al, 2010; Marth et al, 2011]; a robust observation for both SNV and CNV disease associated alleles [Boone et al, 2013]. The overall phenotype of a given individual may to a greater extent represent contribution of either de novo or more recent and private mutational events with bigger effects on the whole system function, the ‘driver’ genes that occurred in the recent ancestors of the individual or clan [Lupski et al, 2011], rather than more distributed common variants shared in a population or throughout several populations.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide approaches have shown that rare variants are more common than previously thought [Coventry et al, 2010; Marth et al, 2011]; a robust observation for both SNV and CNV disease associated alleles [Boone et al, 2013]. The overall phenotype of a given individual may to a greater extent represent contribution of either de novo or more recent and private mutational events with bigger effects on the whole system function, the ‘driver’ genes that occurred in the recent ancestors of the individual or clan [Lupski et al, 2011], rather than more distributed common variants shared in a population or throughout several populations.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions would lead to a hemizygous allele at corresponding genomic regions and contribute to the allelic architecture of both carrier and recessive disease-causing mutations (Boone et al 2013; Flipsen-ten Berg et al 2007). The recent report of a compound inheritance model in congenital scoliosis (CS) provides a model to simulate this particular scenario (Wu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of CNVs in most of these other disorders is unknown. It has been reported that CNVs contribute to 15% of both non-syndromic deafness [65] and retinal dystrophies [66,67], approximately 10% of congenial heart disease [68], partly because CNVs can often be identified in known recessive disease genes [18]. Traditionally, these disorders do not include CNV screening as part of their standard clinical practice and focus primarily on SNV and InDel detection.…”
Section: Cnvs In Patient Cohorts Without Intellectual Disabilitymentioning
confidence: 99%
“…The current generation of genomic microarrays contain hundreds-of-thousands to millions of probes that are able to detect CNVs ranging in size from 1 to 10 kilobases (kb) up to several megabases [7]. Many smaller pathogenic (intragenic) CNVs are known to occur but often remain beyond the detection limit of most clinical genomic microarray analyses [18,19].…”
mentioning
confidence: 99%